Parametric Modeling of a Magnetorheological Engine Mount Based on a Modified Polynomial Bingham Model - Chen, Shiwei; Li, Rui; Du, Pengfei; Zheng, Hengwei; Li, Dingyu (Frontiers in Materials, 2019)
This paper mainly deals with the establishment of the phenomenological mechanical model for a magnetorheological(MR) engine mounts under frequency variation and magnetic variation effects. Firstly, the mounts’ reaction force is divided into three parts in this paper: a Coulomb damping force, an elastic reaction force and a viscous damping force. Then, by using correlation analysis on these forces with frequency and magnetic field, a modified polynomial Bingham parameterized model is proposed in this paper. This model takes external current and external loading frequency as the variables. And by analyzing the relationship between energy dissipation and storage caused by the external displacement excitation, then an identifying method is proposed to identify the nine parameters in the model. Based on this model, an experimental scheme is designed, and the force-displacement relationship of a typical MR mount under different working conditions is tested through the experiment in this paper. According to the proposed method in this paper, the relationship of the reaction force of a MR mount with current and external loading frequency was obtained. The experimental results show that the proposed model can correctly reflect the wide-frequency dynamic characteristics of the mounts in dynamic stiffness, lagging angle and hysteretic curve.